PENERAPAN METODE AHP DALAM PEMILIHAN GURU TELADAN MENGGUNAKAN PHP DAN MYSQL PADA SDIT INSAN KAMIL - Afri Wibowo (Journal Transformation of Mandalika, e-ISSN: 2745-5882, p-ISSN: 2962-2956, 2022)
The process that is still being carried out at SDIT Insan Kamil is still done manually, namely based on observations from the principal directly by appointing teachers who are judged to have potential based on predetermined criteria such as having special achievements, having leadership qualities, activeness in school, absenteeism, have extracurricular and peer relations. The application of this method is considered ineffective because it will cause internal conflicts among teachers and some parties will feel disadvantaged. Based on this, a system will be built that can facilitate the process of assessing outstanding teachers. The method used in the decision support system to determine outstanding teachers is the AHP method for the weighting of the criteria and the MOORA for the ranking. The Analytical Hierarchy Process (AHP) was developed by Dr. Thomas L. Saaty of the Wharton School of Business in the 1970s to organize information from judgment in having the most preferred alternative. Basically the AHP method is a method for solving a complex and unstructured problem into groups, organizing these groups into a hierarchical arrangement, entering numeric values ​​as a substitute for human perception in doing relative comparisons and finally with a synthesis determined elements that have highest priority (saaty, 1990 in Tominanto, 2012). Assessment of teacher performance at SDIT Insan Kamil has so far conducted an assessment of teacher performance which is carried out twice a year or every semester. Performance appraisal is carried out by school supervision, in this case the head of the study program or vice principal in the curriculum field whose system visits each class according to the super vision schedule that has been made. An assessment of the performance of their teaching staff was carried out directly in the KBM, besides that, several supporting data reports were also used regarding the performance of each teacher such as attendance attendance, teaching time attendance, teacher willingness to take part in school events held, etc